Impact of Transportation Linking Projects on Student Competency Development - Ortega Ortega, Josue; García-Ramírez, Yasmany; Díaz Muñoz, Fabian Patricio (European Public & Social Innovation Review, 2025)
Introduction: Linking projects have become integral to Higher Education in Ecuador, necessitating thorough planning, budgeting, continuous monitoring, and rigorous presentation of outcomes. This study evaluates the impact of such projects on student competency development and society, focusing on the Logistics and Transportation Engineering program at Universidad Técnica Particular de Loja (UTPL). A linking project conducted between October 2023 and February 2024 aimed to enhance public transportation in underserved areas of Loja. Methodology: Methodology involved ten seventh-semester students who conducted a detailed analysis of Loja's urban transportation system using advanced tools to assess demand, service schedules, and route availability. Subsequent stages included designing efficient transportation routes and presenting proposals to stakeholders. Results: Results indicate significant improvements in students' technical skills, project management, and communication and teamwork abilities, alongside heightened social responsibility and community engagement. Discussions: This research underscores the pivotal role of linking projects in fostering holistic student development and addressing societal needs through practical application. Conclusions: The study's findings highlight the transformative impact of linking projects on student learning outcomes and their ability to contribute meaningfully to societal challenges, particularly in the context of public transportation development.